2020
DOI: 10.3389/fmicb.2020.01139
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Meconium Microbiome in Dizygotic and Monozygotic Twins Born by Caesarean Section (CS)

Abstract: The early-life microbiota triggers life-long effects on physiological functions and health disorders. Previous studies in adult twins or animal models have revealed associations between host genetics and the harmonious microbiota. However, such associations may be obscured by the fact that each intra-pair of twins will continually encounter various environmental factors as they grow up. Here, we collected the meconium samples from nineteen dizygotic pairs (DZ, n = 38) and nine monozygotic pairs (MZ, n = 18) wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 54 publications
1
10
1
Order By: Relevance
“…Furthermore, most preterm infants delivered by cesarean section have a higher abundance of Proteobacteria than do full-term infants (12,17,25,34), which is consistent with our finding that Proteobacteria was predominant during the T1 stage. It should be noted that our results differ from previous reports that the gut microbiome of newborns during early life had low diversity or was sterile (12,27,(37)(38)(39). Also, DNA extraction methods may affect the determination of microbiome diversity in low biomass samples, which should be further studied in future.…”
Section: Discussioncontrasting
confidence: 90%
“…Furthermore, most preterm infants delivered by cesarean section have a higher abundance of Proteobacteria than do full-term infants (12,17,25,34), which is consistent with our finding that Proteobacteria was predominant during the T1 stage. It should be noted that our results differ from previous reports that the gut microbiome of newborns during early life had low diversity or was sterile (12,27,(37)(38)(39). Also, DNA extraction methods may affect the determination of microbiome diversity in low biomass samples, which should be further studied in future.…”
Section: Discussioncontrasting
confidence: 90%
“…Each infant had faecal samples from at least 3 days after birth. Sampling was conducted following a previously published protocol 14. Approximately 1–1.5 g faecal samples were sampled using a sterile plastic spoon and then placed in sterile tubes under strict aseptic conditions.…”
Section: Methodsmentioning
confidence: 99%
“…Twins, with their high genetic and environmental resemblance, are excellent model for disentangling the effect of genetic and environmental factors on shaping the gut microbiota. For example, a few twin studies have investigated the genetic determinants of the gut microbiota 14 15. However, knowledge on the impact of intrauterine environment on early-life gut microbiota remains largely unknown to date.…”
Section: Introductionmentioning
confidence: 99%
“…For example, recently it was reported that 97% of microbiome phenotypes in wild baboons were significantly heritable [142]. In humans, because the overall similarity of gut bacterial community composition between adult mono-and di-zygotic twin pairs is largely the same, it is reasonable to conclude that physical contact during and after birth has a greater influence as compared to genetic relatedness, in determining gut microbial composition [143,144]. Although it is not clear how much of the human gut microbiome is transferred from mother to infant, several groups of bacteria, such as specific strains of Bifidobacterium breve and Lactobacillus plantarum, were shown to be always present in the infant gut and their mothers' feces and milk [145][146][147], providing direct support for accurate vertical transmission of these strains.…”
Section: Physical Contactmentioning
confidence: 99%